ENGLISH MASSIVE CASE STUDY - Zulkarnain, M. Ervan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Along with the development of technology, mastery of English has become very important in various fields, but the material provided at school is deemed insufficient. This study aims to: (1) determine the learning process carried out by English Massive in an English learning environment, and (2) the students-teacher relationship during teaching activities. This study used a qualitative approach (observation and semi-structured interviews). The subjects in this study were English Massive management, 3 tutors, and 3 students from different levels. The finding indicated that: (1) English Massive spots were spread throughout Kerdiri City. English Massive develops its own curriculum, syllabus, and module books which are used as a reference in teaching. Young Learner learning activities incorporate several games to keep them interested, while in the Young Adult class, learning is more focused on material and discussion to develop their speaking skills. (2) The relationship between teacher and student during learning varies depending on the level. Tutors and students in the Young Learner class are like big brother and little brother relations. On the other hand, Young Adults and Adults consider their tutors like companions with whom they feel comfortable sharing their ideas.